2008
DOI: 10.1111/j.1601-6343.2008.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐energy laser stimulates tooth movement velocity via expression of RANK and RANKL

Abstract: These findings suggest that low-energy laser irradiation stimulates the velocity of tooth movement via induction of RANK and RANKL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
124
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 39 publications
9
124
0
16
Order By: Relevance
“…These effects are due to its ability to stimulate cell metabolism, angiogenesis, bone formation and osteoclastogenesis (Garnero et al, 1994;Fassbender et al, 2009;Fujita et al, 2008.;Fujiyama et al, 2008;Habib et al, 2012;Genc et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These effects are due to its ability to stimulate cell metabolism, angiogenesis, bone formation and osteoclastogenesis (Garnero et al, 1994;Fassbender et al, 2009;Fujita et al, 2008.;Fujiyama et al, 2008;Habib et al, 2012;Genc et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%
“…Fujita et al [20] found that PBM with LED does not stimulate tooth movement while PBM with laser does. Elke et al [33] reported significantly different fibroblast proliferations when applying PBM with different wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…22 Although most of the protocols used for applying LLL during OTM are punctual, there are variations in the wavelengths, doses and the number of irradiation sessions. Some authors have used daily irradiations of LLL, 4,11,15 while others have set different intervals of laser application. 2,13,22 Considering that the effect of laser is dose-dependent, 6,10 greater attention should be given to the irradiation protocols.…”
mentioning
confidence: 99%
“…18 Furthermore, studies that observed an increase in OTM with daily laser irradiation have demonstrated that the rate of OTM rises between the second and third days, keeping a constant difference between groups after this period. 4,11 Thus, it is necessary to test protocols for LLL application which include irradiation only in the initial stage of OTM.…”
mentioning
confidence: 99%